Are tax and expenditure limitations constraining institutions or institutionally irrelevant? Evidence from Minnesota. (17th October 2022) - Shumberger, Jason; Singla, Akheil
Abstract: State‐imposed limitations on local government taxation and expenditures (TELs) are a common part of American federalism. But the consequences of TELs are the subject of debate. Are TELs institutional constraints that harm local governments? Or are TELs institutionally irrelevant veils easily pierced by political actors? This research uses the removal of an assessment restriction in Minnesota to evaluate the effect of TELs on the financial health of local governments. It finds that TEL removal had no effect on the financial health of Minnesota cities. Additional tests demonstrate that the results are not driven by a lack of bindingness in the TEL, by increases in property tax rates, or by new non‐property tax revenue. It concludes that TELs are closer to institutionally irrelevant than to meaningful constraints. Applications for Practice: States regularly impose tax and expenditure limitations (TELs) on their local governments. Many have argued that these limitations harm local government finances by restricting local autonomy. We find little evidence of that harm. Minnesota local governments saw no discernable improvements to their financial health following the removal of an assessment restriction. When focusing only on local governments that were likely bound by the TEL, we still find no clear effect of removing the TEL. We also show that nonproperty tax revenue generation was unaltered by the policy change. State‐imposed TELs may have little to no effect on the financial health of local governments.